GmERF57 negatively regulates root development and phosphate absorption in soybean - Hongqing Zhu; Dandan Hu; Yifei Yang; Xuhao Zhai; Shanshan Zhang; Mengshi He; Huifang Zuo; Lina Zhang; Mengjun Xu; Shanshan Chu; Haiyan Lü; Hengyou Zhang; et al. (Plant Stress)
Low soil phosphate (Pi) availability is a primary limiting factor for crop growth and production due to its immobilization in soil, thereby impeding Pi uptake by plants. However, excessive supply of phosphorus fertilizer can result in eutrophication of water bodies. Therefore, improving Pi utilization and uptake efficiency in plants is crucial for sustainable agriculture. Previously, we identified soybean Ethylene Response Factor 57 (GmERF57) as a candidate gene responsible for q20, a major QTL associated with soybean low Pi (LP) tolerance-related traits identified through QTL mapping and genome-wide association analysis (GWAS). Population genomics analysis revealed that GmERF57 has undergone artificial selection, and allelic distribution analysis significantly correlated with traits associated with LP tolerance in soybean. Haplotype 2 (Hap2), carrying the T to C single nucleotide polymorphism (SNP), represents the optimal allele favoring LP tolerance. Silencing GmERF57 expression promoted root development and enhanced plant Pi uptake; conversely, overexpression of GmERF57 yielded contrasting phenotypes compared to silenced roots. We further uncovered that GmERF57 physically interacts with GmTUB1 (β-tubulin protein) and modulates soybean root architecture and Pi uptake capacity by downregulating GmTUB1 and other Pi starvation response genes. Overall, the results identified GmERF57 as a QTL gene associated with LP tolerance, elucidated its role in regulating LP tolerance, and further identified an optimal haplotype to facilitate breeding of LP-tolerant soybean cultivars.